2009
DOI: 10.1177/1356336x09105213
|View full text |Cite
|
Sign up to set email alerts
|

Sport Education for Teachers: Professional Development When Introducing a Novel Curriculum Model

Abstract: The purpose of this study was to provide a description of an on-site professional development program for Russian teachers as they learned to teach Sport Education. A concurrent objective was to investigate the effectiveness of this professional development opportunity. Participants were two physical education teachers (one with 27 and one with 3 years of experience) who taught separate sixth grade physical education classes in a school in the Central Chernozem Region of Russia. The data sources included the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 35 publications
(47 reference statements)
2
58
0
16
Order By: Relevance
“…While this need for 'hard evidence' was only specifically mentioned in four of the studies in primary/elementary schools (Dyson and Rubin 2003;Kinchin, MacPhail, and Chroinin 2009;Sinelnikov 2009;Walsh, Ozaeta, and Wright 2010) the fact that these projects occurred in three countries (USA, Ireland and Russia) and across three models (Cooperative Learning, Sport Education and Teaching Personal and Social Responsibility) increases the significance of this finding. Furthermore, when this desire for evidence is viewed in light of concerns that primary school teachers received too few hours during their training in physical education and that MBP is still considered as innovative practice, it suggests that that this topic warrants further discussion.…”
Section: Evidence Of Effectivenessmentioning
confidence: 98%
See 3 more Smart Citations
“…While this need for 'hard evidence' was only specifically mentioned in four of the studies in primary/elementary schools (Dyson and Rubin 2003;Kinchin, MacPhail, and Chroinin 2009;Sinelnikov 2009;Walsh, Ozaeta, and Wright 2010) the fact that these projects occurred in three countries (USA, Ireland and Russia) and across three models (Cooperative Learning, Sport Education and Teaching Personal and Social Responsibility) increases the significance of this finding. Furthermore, when this desire for evidence is viewed in light of concerns that primary school teachers received too few hours during their training in physical education and that MBP is still considered as innovative practice, it suggests that that this topic warrants further discussion.…”
Section: Evidence Of Effectivenessmentioning
confidence: 98%
“…However, the evidence of their own eyes and experiences was enough to leave them delighted with both the outcome and its appropriateness as a conclusion to their endeavours. In his work with Russian teachers through Sport Education Sinelnikov (2009) found that pedagogical and curricular change was further facilitated by an evidence-based showing the successes of other practitioners and that teachers needed to see the results of their peers efforts to believe in the potency of the model. Walsh et al (2010) reported that despite the transfer of learning that occurred across contexts by using the Teaching Personal and Social Responsibility model, teachers in the USA were reluctant to attribute the success to the model.…”
Section: Evidence Of Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…En este sentido, se desarrolló un seminario de 12 sesiones de una hora en el cual se abordaron aspectos teóricos y prácticos del modelo de Educación Deportiva. Un investigador externo evaluó la correcta aplicación del programa en el grupo experimental, siguiendo para ello la hoja de registro observacional de Ko, Wallhead, y Ward (2006), utilizada en anteriores investigaciones (García-López y Sinelnikov, 2009). El profesor que llevó a cabo la intervención cumplió todos los indicadores de la hoja de registro.…”
Section: Diseño Y Validación De Los Programas De Intervenciónunclassified